CO2 storage behavior of rice husk biochar-bitumen mixture at different pressures and temperatures: a detailed experimental investigation - Kumar, Kondapaka Kishor; Omal, N. M.; Sharma, Vinod Kumar; Kandy, Sharu Bhagavathi; Agbulut, Umit (SPRINGER, 2025)
Overutilization of fossil fuels has led to elevated levels of atmospheric CO2, which presents substantial risks to global warming and climate change. The most effective way to address this issue is through the capture and use of carbon dioxide (CO2). In this regard, in the present study, an adsorption technique is chosen for CO2 capture whereas activated rice husk biochar (ARHBC) is synthesized as an adsorbent. In addition, two more samples, i.e., pure bitumen and its mixture with 6% ARHBC are prepared to study their CO2 adsorption behavior at near ambient conditions. The physical characterization, i.e., BET, FTIR, XRD, SEM, EDS, and TGA analyses, of these adsorbents are carried out which results in the favor of their suitability toward CO2 adsorption showing the BET surface area of 2492.9 m(2) g(-1), thermal stability, and high porosity. In addition, the strength (softening point, penetration, and ductility) of the bitumen-ARHBC mixture is tested to confirm its suitability for construction applications and found to be higher than the minimum permissible values. Later, all three adsorbents are tested for CO2 storage capabilities using a volumetric method-based apparatus at different temperatures and pressures. The CO2 adsorption test results in 0.33 gm gm(-1) of ARHBC, 0.05 gm gm(-1) of mixture, and 0.02 gm gm(-1) of pure bitumen at 25 degrees C and 4.5 bar. The obtained CO2 adsorption capacity of ARHBC, i.e., 3.1 mmol/gm at 1 bar and 25 degrees C is observed to be similar to the results in the literature. It is suggested that the mixture's adsorption capacity can be increased by increasing the ARHBC content till the permissible limit.
Keywords: Adsorption; Biochar; Bitumen; CO2 capture; Isotherm; Adsorbent; ACTIVATED CARBON; POROUS CARBONS; CAPTURE; ENERGY; SEQUESTRATION; ADSORBENTS; EQUILIBRIUM; KINETICS; Thermodynamics; Chemistry